Evolution Of A New Financial Architecture Through The Liberalisation Of Financial Services - Tie, Fatt Hee (Journal of Malaysian and Comparative Law, 2001)
This discussion would examine the aim of the multilateral negotiations on trade in services set out in the GATS. It would consider the recent measures that have been adopted by some of the regional organisations to fulfil their commitments. It would also examine the reforms that have been recommended for the implementation of the GATS in respect of financial services. It would discuss the possible impact of these reforms on member countries. The economic crisis in countries such as Chile, Russia and in the Southeast Asian region have led to general reluctance on the part of some countries to commit themselves fully to the obligations laid down in the GATS.